2017
DOI: 10.3748/wjg.v23.i45.8008
|View full text |Cite
|
Sign up to set email alerts
|

Albumin as a prognostic marker for ulcerative colitis

Abstract: AIMTo evaluate the role of albumin at the time of ulcerative colitis (UC) diagnosis in predicting the clinical course of disease.METHODSNationwide cohort of patients with newly diagnosed UC in the Veterans Affairs health care system was identified and divided into two categories: hypoalbuminemia (i.e., ≤ 3.5 gm/dL) or normal albumin levels (i.e., > 3.5 gm/dL) at the time of UC diagnosis. The exposure of interest was presence of hypoalbuminemia defined as albumin level ≤ 3.5 g/dL at the time of UC diagnosis. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 37 publications
2
33
0
2
Order By: Relevance
“…Candidate factors associated with the long-term outcomes of tacrolimus therapy in the multivariate Cox regression model were the sex (14), age at the diagnosis (14), concomitant IM, steroid dependency, albumin (15), and disease location (16), These factors were previously reported to be associated with the clinical course of UC. Interactions among these 6 factors in the multivariate analysis revealed concomitant IM to be an independent protective factor for relapse (adjusted HR: 0.35, 95% CI: 0.16-0.78, p=0.01), while the other 5 factors were not significantly associated with increased risks of clinical relapse (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Candidate factors associated with the long-term outcomes of tacrolimus therapy in the multivariate Cox regression model were the sex (14), age at the diagnosis (14), concomitant IM, steroid dependency, albumin (15), and disease location (16), These factors were previously reported to be associated with the clinical course of UC. Interactions among these 6 factors in the multivariate analysis revealed concomitant IM to be an independent protective factor for relapse (adjusted HR: 0.35, 95% CI: 0.16-0.78, p=0.01), while the other 5 factors were not significantly associated with increased risks of clinical relapse (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Using this model, we demonstrated that the administration of r-Alb potently prevented the onset and progression of the disease. In patients with colitis, the amount of plasma Alb is decreased because of the chronic inflammation in the intestinal tract, and the antioxidative capacity of Alb is also weakened due to the oxidative modification [ 22 , [31] , [32] , [33] ]. As a bioproduct, Alb is used in many clinical situations.…”
Section: Discussionmentioning
confidence: 99%
“…In both experimental model and IBD patients, the serum level of Alb is reported to be decreased, whereas the oxidized Alb is increased [ 22 , [31] , [32] , [33] ]. Furthermore, the altered Alb is closely correlated with inflammatory activity and has been proposed as prognostic marker of UC diagnosis [ 31 ]. In these backgrounds, we, therefore, hypothesized that the supplement of Alb, especially the reduced Alb, could have a beneficial therapeutic effect on IBD.…”
Section: Introductionmentioning
confidence: 99%
“…In patients who have hypoalbuminemia, though feeding is an important supportive measure, nutritional support alone is very unlikely to restore low albumin levels. The evidence to support the use of intravenous albumin is poor and underlying sepsis and inflammation should be adequately controlled [ 208 ]. In elective surgery, the early/enhanced recovery after surgery protocol should be followed in the perioperative period …”
Section: The Asian Working Group Guidelines Regarding Diet In Inflammmentioning
confidence: 99%